Mixed Ensemble Learning In Extracurricular Student Of SMPN 15 Palembang (Jurnal Seni Musik, 2021)
This study aims to describe mixed ensemble learning in extracurricular activities in class IX students of SMP Negeri 15 Palembang. The research method used is descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation. The preparation of the trainer before doing the learning is to determine the material that is taught to students at each meeting, then the trainer determines the strategies and learning methods that will be used in learning so that learning objectives are achieved. The implementation of mixed ensemble learning at SMP Negeri 15 Palembang includes; 1) The mixed ensemble learning process consists of group division, placement and selection of musical instruments, learning for each instrument, 2) Mixed ensemble learning includes three stages, namely preparation, implementation, and evaluation